A differential equation for polynomials related to the Jacobian conjecture - Valqui Haase, Christian Holger (2013)
We analyze a possible minimal counterexample to theJacobian Conjecture P;Q with gcd(deg(P); deg(Q)) = 16 and show that its existence depends only on the existence of solutions for a certain Abel dierential equation of the second kind.